Observing Fennoscandian Gravity Change by Absolute Gravimetry - Timmen, Ludger; Gitlein, Olga; Müller, Jürgen; Denker, Heiner; Mäkinen, Jaakko; Bilker, Mirjam; Pettersen, Bjørn Ragnvald; Lysaker, Dagny I.; Omang, Ove Christian Dahl; Svendsen, J. G. G.; Wilmes, Herbert; Falk, Reinhard; et al. (2006)
The Nordic countries Norway, Sweden, Denmark and Finland are a key study region for the research of glacial isostasy, and, in addition, it offers a unique opportunity for validating and testing the results of the GRACE experiment. Over a period of five years, the expected life time of GRACE, a temporal geoid variation of 3.0 mm is expected in the centre of the Fennoscandian land uplift area, corresponding to a gravity change of about 100 nm/s2. This is expected to be within the detection capabilities of GRACE. With terrestrial absolute gravimetry, the gravity change due to the land uplift can be observed with an accuracy of ±10 to 20 nm/s2 for a 5-year period. Thus, the terrestrial insitu observations (ground-truth) may be used to validate and test the GRACE results.Since 2003, absolute gravity measurements have been performed in Fennoscandia at about 30 stations covering Norway, Sweden, Finland and Denmark. Four groups with FG5 absolute gravimeters (BKG, FGI, IfE, UMB) are engaged to survey the uplift network annually by a mutually controlled procedure. Nearly all absolute stations are colocated with permanent GPS stations. From the 2003 and 2004 comparisons between the instruments, an overall accuracy of ±30 nm/s2 is indicated for a single absolute gravimeter and a single station determination. This is in full agreement with the project goal.